ACU&MOX-DATA: a platform for fusion analysis and visual display acupuncture multi-omics heterogeneous data. Issue 1 (12th January 2023) - Wu, Qiaofeng; Liu, Shuqing; Zhang, Ruibin; Tang, Qiang; Dong, Longcong; Li, Sihui; Yu, Shuguang
Abstract : A new network platform named ACU&MOX-DATA (http://cbcb.cdutcm.edu.cn/ACU&MOX-DATA/ ) was recently set up and introduced. The purpose of this website is to integrate and analyze multi-omics data of acupuncture and moxibustion and serve as a disease, clinical, and laboratory experiment public database. Some existing functions and the future plan of the website were also discussed. This platform can help researchers to integrate analyses and visual interpretation of key scientific issues in acupuncture & moxibustion under the guidance of traditional Chinese medicine theory through heterogeneous and multi-level data fusion analysis. Graphical abstract: http://links.lww.com/AHM/A41 . Abstract :